THE INVESTIGATION OF ENGLISH GRAMMAR LEARNING STRATEGY ON HIGH, MIDDLE, AND LOW ACHIEVERS' STUDENTS IN INDONESIA - Regita Cahyani; Muhammad Ridhuan Tony Lim Abdullah; Cahya Komara (ELLTER Journal, 2022)
This study investigates the English grammar learning strategy used among high, middle, and low achievers’ students in Indonesia. The aim is to reveal which types of strategies that high, middle, and low achievers’ students applied most while learning English grammar and to check whether or not there is difference grammar learning strategy used by high, middle, and low achievers’ students. A lot of researchers have concentrated their interest on the grammar learning strategy area, including in Indonesia, however, it was not seen much or still found limited references to check the grammar learning strategy among high, middle, and low achievers’ students. Besides, the grammar learning strategy instruments of other Indonesian researchers are complexly varied. This study is focused on finding the strategies that high, middle, and low achievers’ students used through Pawlak’s Grammar Learning Strategy Inventory or GLSI (2018) with 100 participants (high vs middle vs low achievers’ students) involved. The results showed that there are significant differences between the frequent use of grammar learning strategies between low, middle, and high achievers' students. Social strategies are the most frequently used grammar learning strategies by low and middle achievers’ students, while metacognitive strategies are the strategies most frequently used by high-achieving students in Indonesia.